Laboratory Evaluation of Isaria fumosorosea CCM 8367 and Steinernema feltiae Ustinov against Immature Stages of the Colorado Potato Beetle - Hussein, Hany M.; Skoková Habuštová, Oxana; Půža, Vladimír; Zemek, Rostislav (PLOS ONE, 2016)
The Colorado potato beetle, Leptinotarsa decemlineata, has developed resistance to most registered pesticides and has become one of the most difficult insect pests to control. Development of new biopesticides targeting this pest might solve the resistance problem and contribute to sustainable crop production. Laboratory experiments were conducted to assess the efficacy of Isaria fumosorosea (syn. Paecilomyces fumosoroseus) strain CCM 8367 against L. decemlineata when applied alone or combined with the entomopathogenic nematode Steinernema feltiae. The last-instar larvae of the Colorado potato beetle showed the highest susceptibility to I. fumosorosea followed by pre-pupae and pupae. The median lethal concentration (LC50) was estimated to be 1.03×106 blastospores/ml. The strain CCM 8367 was more virulent, causing 92.6% mortality of larvae (LT50 = 5.0 days) compared to the reference strain Apopka 97, which caused 54.5% mortality (LT50 = 7.0 days). The combined application of the fungus with the nematodes increased the mortality up to 98.0%. The best results were obtained when S. feltiae was applied simultaneously with I. fumosorosea (LT50 = 2.0 days); later application negatively affected both the penetration rate and the development of the nematodes. We can conclude that the strain CCM 8367 of I. fumosorosea is a prospective biocontrol agent against immature stages of L. decemlineata. For higher efficacy, application together with an entomopathogenic nematode is recommended.